Droplet coalescence in microfluidic systems - Xu, Bin (2012)
Droplet coalescence is one of the most attractive manipulation schemes in droplet-based microfluidic systems, which enables droplet-based functions such as mixing and microreactor to be achieved in lab-on-a-chip applications. This paper systematically presents an overview on techniques used for droplet coalescence in microfluidic systems. In this paper, techniques employed for droplet coalescence are categorized as passive and active types. The basic theory and mechanism behind these techniques are also presented.